PERANCANGAN RESORT WISATA PANGURURAN DENGAN TEMA TRANSFORMASI ARSITEKTUR BATAK TOBA - Sigalingging, Hernandes; Sihombing, Sanggam B; Mayono Suko Marbinoto (LPPM ISTP, 2023)
Pangururam is one of the sub-districts of Samosir District. Tourism in Panguruland and Lake Toba is very good. Tourism development is needed to support visitors to Samosir Island. One of them is to develop tourism through the construction of Pangululan tourist resort. How to use the Toba Batak Architectural Transformation theme using the theme. This can also be used to maintain sustainability or introduce tourists to the Toba Batak area The theme of the Pangurulan Tourist Resort architecture is